Uncovering the Signaling Pathway behind Extracellular Guanine-Induced Activation of NO System: New Perspectives in Memory-Related Disorders - Mariachiara Zuccarini; Mariachiara Zuccarini; Patricia Giuliani; Patricia Giuliani; Monica Frinchi; Giuseppa Mudò; Rosa Maria Serio; Natale Belluardo; Silvana Buccella; Silvana Buccella; Marzia Carluccio; Marzia Carluccio; et al. (Frontiers Media S.A., 2018)
Mounting evidence suggests that the guanine-based purines stand out as key player in cell metabolism and in several models of neurodegenerative disorders, such as Parkinson's and Alzheimer's diseases. Guanosine (GUO) and guanine (GUA) are extracellular signaling molecules derived from the breakdown of the correspondent nucleotide, GTP, and their intracellular and extracellular levels are regulated by the fine-tuned activity of two major enzymes, purine nucleoside phosphorylase (PNP) and guanine deaminase (GDA). Noteworthy, GUO and GUA, seem to play opposite roles in the modulation of cognitive functions, such as learning and memory. Indeed GUO, despite exerting neuroprotective, anti-apoptotic and neurotrophic effects, causes a decay of cognitive activities, whereas GUA administration in rats results in working memory improvement (prevented by L-NAME pre-treatment). This study was designed to investigate, in a model of SH-SY5Y neuroblastoma cell line, the signal transduction pathway activated by extracellular GUA. Altogether, our results showed that: (i) in addition to an enhanced phosphorylation of ASK1, p38 and JNK, likely linked to a non-massive and transient ROS production, the PKB/NO/sGC/cGMP/PKG/ERK cascade seems to be the main signaling pathway elicited by extracellular GUA; (ii) the activation of this pathway occurs in a pertussis-toxin sensitive manner, thus suggesting the involvement of a putative G protein coupled receptor; (iii) the GUA-induced NO production, strongly reduced by cell pre-treatment with L-NAME, is negatively modulated by the EPAC-cAMP-CaMKII pathway, which causes the over-expression of GDA that, in turn, reduces the levels of GUA. These molecular mechanisms activated by GUA may be useful to support our previous observation showing that GUA improves learning and memory functions through the stimulation of NO signaling pathway, and underscore the therapeutic potential of oral administration of guanine for treating memory-related disorders.